2020
DOI: 10.1155/2020/7653745
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Barriers Influencing Seasonal Influenza Vaccination Uptake

Abstract: Background. Seasonal influenza is an acute respiratory infection caused by influenza viruses that are highly contagious and circulate in all parts of the world. It gives rise to an estimated 3 to 5 million cases of severe illness and about 250,000 to 500,000 deaths globally each year. Influenza tends to cause epidemics with serious illness and death among high-risk groups such as children aged 5 years and younger, pregnant women, elderly ≥65 years of age, and with chronic medical conditions. According to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 15 publications
(22 reference statements)
2
28
1
1
Order By: Relevance
“…However, a sensitivity analysis showed no significant difference between the baseline age group ( Uwemedimo et al, 2012 , Babalola, 2011 , Babalola and Lawan, 2009 , Chen et al, 2011 , Mapatano et al, 2008;50(2):61-. , Alabbad et al, 2018 , Bednarczyk et al, 2015 , Barry et al, 2020 , Aljamili, 2020 , Alqahtani et al, 2017 ) and > 65 age group. There was also no significant association between the other demographic frequencies, gender and nationality, and awareness of the vaccine ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a sensitivity analysis showed no significant difference between the baseline age group ( Uwemedimo et al, 2012 , Babalola, 2011 , Babalola and Lawan, 2009 , Chen et al, 2011 , Mapatano et al, 2008;50(2):61-. , Alabbad et al, 2018 , Bednarczyk et al, 2015 , Barry et al, 2020 , Aljamili, 2020 , Alqahtani et al, 2017 ) and > 65 age group. There was also no significant association between the other demographic frequencies, gender and nationality, and awareness of the vaccine ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two trained senior pharmacy students administered a predesigned electronic survey and total of 318 adult visitors were interviewed. The survey was adopted from Arabic study and was reviewed by specialized subject matter expert and further piloted among small group of students to ensure capturing local context ( Barry et al, 2020 ). Outcome definition …”
Section: Methodsmentioning
confidence: 99%
“…Most frequent arguments against influenza vaccination included the fear of side effects and allograft injury. The fear of side effects was also a prominent argument in previous questionnaire studies, even in medical staff [ 8 , 25 27 ]. The safety of seasonal trivalent inactivated influenza vaccines as well as the high dose and booster dose has been confirmed in several studies including transplant recipients [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barry et al conducted a study about seasonal influenza vaccines and reported that regarding barriers, 295 participants (58.6%) wanted to avoid seasonal influenza vaccines and 252 (50.1%) were concerned about the vaccine's adverse effects [14]. Wang et al reported that around half of respondents (47.8%) with vaccination intention would delay vaccination until the safety of the COVID-19 vaccine is confirmed, and concerns or uncertainty about vaccine safety led to their vaccine hesitation [15].…”
Section: Resultsmentioning
confidence: 99%
“…This study included an online questionnaire that was conducted to explore the barriers influencing COVID-19 vaccination uptake among the public in Saudi Arabia. The questionnaire was prepared using a validated questionnaire of previous study conducted by Barry et al about seasonal influenza vaccination [14]. After that, it was converted using Google ® forms to an online form and was disseminated by social media platforms (mainly Instagram) to be completed by the public.…”
Section: Methodsologymentioning
confidence: 99%